WATER SUPPLY SYSTEM AND SOLID WASTE MANAGEMENT FOR LASONA VILLAGE - MAGAR P.D.; PROF. HANGARGEKAR P.A. (International Journal of Innovations in Engineering Research and Technology, 2021)
This paper includes watersupply scheme andSWM forLasona village. Watersupplied to the peoples isimpure in nature and without any treatmentinLasona village. Waterdistribution system is not provided, villagers have to collect water from various water tanks this is waste of man hours and increasesconflict related to water.In present work an effective pattern for rural water supply hasbeen designed and elaborated.SWMin village is another environmentalproblem faced by rural population. Thispapergivesa composting as a treatment method for the solid waste generated. A composting yard hasbeen designed and its estimates have been prepared.Total cost requiredfor water supply and SWM is calculated be4041.62 rs and 468.40 rs as per existing SSR and market rates.